2020
DOI: 10.1021/acs.bioconjchem.0c00590
|View full text |Cite
|
Sign up to set email alerts
|

DiPODS: A Reagent for Site-Specific Bioconjugation via the Irreversible Rebridging of Disulfide Linkages

Abstract: Chemoselective reactions with thiols have long held promise for the site-specific bioconjugation of antibodies and antibody fragments. Yet bifunctional probes bearing monovalent maleimideslong the “gold standard” for thiol-based ligationsare hampered by two intrinsic issues: the in vivo instability of the maleimide–thiol bond and the need to permanently disrupt disulfide linkages in order to facilitate bioconjugation. Herein, we present the synthesis, characterization, and validation of DiPODS, a novel bioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In this investigation, we have harnessed an emergent, thiol-reactive bioconjugation reagent based on a p henyl o xa d iazolyl methyl s ulfone (PODS) core to create a site-specifically modified 89 Zr-radioimmunoconjugate as a companion diagnostic for a DLL3-targeted antibody–drug conjugate (ADC). PODS-based reagents react quickly, cleanly, and (unlike maleimides) irreversibly with thiols (Figure A). Even more importantly, we have previously demonstrated that the site-selective modification of wild-type antibodies with PODS-bearing chelators produces 177 Lu- and 89 Zr-labeled radioimmunoconjugates with high stability and excellent in vivo performance (Figure B) …”
mentioning
confidence: 99%
“…In this investigation, we have harnessed an emergent, thiol-reactive bioconjugation reagent based on a p henyl o xa d iazolyl methyl s ulfone (PODS) core to create a site-specifically modified 89 Zr-radioimmunoconjugate as a companion diagnostic for a DLL3-targeted antibody–drug conjugate (ADC). PODS-based reagents react quickly, cleanly, and (unlike maleimides) irreversibly with thiols (Figure A). Even more importantly, we have previously demonstrated that the site-selective modification of wild-type antibodies with PODS-bearing chelators produces 177 Lu- and 89 Zr-labeled radioimmunoconjugates with high stability and excellent in vivo performance (Figure B) …”
mentioning
confidence: 99%
“…They reported a superior stability compared to cysteine maleimide conjugates in human plasma [ 118 , 119 ]. Inspired by this report, Zeglis designed the reagent DiPODS for site-specific, irreversible bioconjugation on native antibodies fragment Fab [ 120 , 121 , 122 ]. This reagent contains two oxadiazolyl methyl sulfone moieties connected by a phenyl group.…”
Section: Bioconjugationmentioning
confidence: 99%
“…29–31 These linkers contain two cysteine-reactive groups that may undergo reaction with reduced interchain disulfides in an IgG molecule to effect covalent rebridging of the antibody chains in a site-selective fashion. Next-generation maleimides (NGMs), 32,33 pyridazinediones, 34 bissulfones, 35 divinylpyrimidine (DVP) 36–39 and a variety of other reagents 40–44 have been used to modify antibodies in this way. However, the utility of this approach is currently hampered by the formation of fragmented “half-antibody” species during bioconjugation, which is the result of non-native intrachain cross-linking of the cysteine residues in the hinge region of the antibody (Fig.…”
Section: Introductionmentioning
confidence: 99%